Geliat Pariwisata Wellness Tourism Dalam Masa Pandemi - Umar Abdul Jabbar; Andhi Supriyadi (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
One of the industries that has been badly impacted by the COVID-19 outbreak is tourism. According to BPS statistics from 2021, there has been a dramatic drop in both domestic and international tourism. Diverse initiatives are made to keep Indonesian tourism alive. Kemenparekraf/Baparekraf is in charge of the "rescue" phase's emergency response, recovery, and normalization. According to Kaspar, wellness tourism is a type of tourism service that can be produced or enhanced in response to a destination's social and environmental circumstances. In terms of the tourist industry, wellness tourism is a subset of health tourism that is comparable to other tourism industries. Here are some motivational ideas that were examined based on the push and pull variables used in this study However, push factors do not considerably increase the desire to travel for wellness in Indonesia. Push factors might be said to cause the urge to return to traveling for wellbeing. According to reports, pull factors significantly influence foreign tourists' interest in visiting Indonesia for wellness tourism. Enhancing mental wellbeing is the indicator that best explains the push factors for tourists to engage in wellness tourism in Indonesia, whilst heritage and culture are the indicator that best describes the draw factors. However, out of the two, pull factors have a greater impact on tourists' interest in visiting.